2016
DOI: 10.1007/s00394-016-1236-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between food and beverage consumption and different types of sedentary behaviours in European preschoolers: the ToyBox-study

Abstract: In European preschoolers, sedentary behaviours were associated with consumption of energy-dense foods and fizzy drinks. The present findings will contribute to improve the strategies to prevent overweight, obesity and nutrition-related chronic diseases from early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Analysing the relation between SST and dairy consumption, few studies have taken into consideration dairy food types. In European pre-school children, exceeding total screen time recommendations, established at 1 hour per day, was positively associated with increased consumption of sweetened milk (29). In another study, the use of internet during weekends was negatively associated with milk consumption in European adolescents of both genders.…”
Section: Discussionmentioning
confidence: 89%
“…Analysing the relation between SST and dairy consumption, few studies have taken into consideration dairy food types. In European pre-school children, exceeding total screen time recommendations, established at 1 hour per day, was positively associated with increased consumption of sweetened milk (29). In another study, the use of internet during weekends was negatively associated with milk consumption in European adolescents of both genders.…”
Section: Discussionmentioning
confidence: 89%
“…Similar associations were observed in European adolescents [42]: Those adolescents with the lowest PA levels consumed fewer fruits and dairy products compared to active adolescents. In a previous publication of the ToyBox study, those exceeding baseline ST recommendations had a higher consumption of energy-dense foods (sugar-based desserts, salty snacks, pastries, cakes, and biscuits) and beverages (fizzy drinks, sweet milk, and juices) than those complying with ST recommendations [12]. Another study reported that high TV viewing was related to less healthy food options (consumption of sweets and soft drinks) in children from different countries [43].…”
Section: Discussionmentioning
confidence: 99%
“…ST has been shown to be associated with increased energy-dense food and beverage consumption and decreased fruit and vegetable (F & V) consumption in preschool children [12]. In European children participating in the IDEFICS study, low time spent on moderate to vigorous physical activity (MVPA) was associated with a low consumption of vegetables and yogurt and high fast food consumption [13].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional interventions aimed at influencing fruit and vegetable intake among young people do not show extraordinary results [ 23 ]. There are few health applications that use gamification as an educational resource [ 24 ].…”
Section: Introductionmentioning
confidence: 99%